PENGARUHEKUITAS MEREK DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN PRODUK “FRISIAN FLAG UHT LOW FAT & HIGH CALCIUM” (Studi Kasus pada Lotte Mart, Semarang) - Muhaddyatma Wiraliosojati; Sri Suryoko; Saryadi Saryadi (Jurnal Ilmu Administrasi Bisnis, 2014)
Dairy beverage industry company PT . Frisian Flag is introducing dairy products under the brand through advertising flag with electronic media . Thus it is imperative for companies such as dairy beverage processing PT.Frisian Flag that produce milk with a brand flag to know the behavior of consumers , in order to implement brand development strategy is mainly associated with a media campaign that also will be used further in the future . This study aims to : ( 1 ) To determine the effect of brand equity on purchase decisions flag dairy products . ( 2 ) To determine the effect of promotions on purchase decisions flag dairy products . ( 3 ) To determine the effect of brand equity and promotion of dairy product purchasing decisions flag . This type of research is quantitative research , the technique of collecting data through questionnaires . The sampling technique used judgement sampling technique , the sample of 100 people who consume milk flag Frisian Flag UHT Low Fat & High Calcium in Semarang . The analytical method used was simple and multiple regression analysis , the validity and reliability .Based on the analysis , the conclusion is : ( 1 ) Variable FF UHT milk brand equity LF & HC classified in the high category . ( 2 ) Variable UHT milk promotion FF LF & HC is good . ( 3 ) a decision variable purchase UHT milk LF FF & HC is fair. ( 4 ) brand equity variables have an influence on purchase decision variable of 0.248 . ( 5 ) promotion variables have an influence on purchase decision variable that is equal to 0.278 . ( 6 ) and promotion of brand equity variables have an influence on the purchase decision of .760 .